2011
DOI: 10.1364/ol.36.001467
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of high-power solitons in saturable nonlinear photonic lattices

Abstract: We theoretically study the properties of one-dimensional nonlinear saturable photonic lattices exhibiting multiple mobility windows for stationary solutions. The effective energy barrier decreases to a minimum in those power regions where a new intermediate stationary solution appears. As an application, we investigate the dynamics of high-power Gaussian-like beams finding several regions where the light transport is enhanced.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Therefore, the effective size of this solution will drastically decrease being, for some value of the norm, smaller than the ring solution. We may thus expect an exchange of fundamental properties between the ring and the one-peak solutions if compared at a given norm (cf, e.g., similar features for saturable systems, where multiple changes on the effective size of fundamental solutions result in stability exchanges [18][19][20]). We construct the family of one-peak solutions by implementing a multi-dimensional Newton-Raphson iterative method [1], demanding a (norm-square) accuracy of at least 10 −15 .…”
mentioning
confidence: 98%
“…Therefore, the effective size of this solution will drastically decrease being, for some value of the norm, smaller than the ring solution. We may thus expect an exchange of fundamental properties between the ring and the one-peak solutions if compared at a given norm (cf, e.g., similar features for saturable systems, where multiple changes on the effective size of fundamental solutions result in stability exchanges [18][19][20]). We construct the family of one-peak solutions by implementing a multi-dimensional Newton-Raphson iterative method [1], demanding a (norm-square) accuracy of at least 10 −15 .…”
mentioning
confidence: 98%
“…Discrete nonlinear dispersive systems arise in nonlinear optics, e.g. [2,1,10,11,35,55,53], the dynamics of biological molecules, e.g. [7,9], and condensed matter physics.…”
mentioning
confidence: 99%
“…Many works have followed discussing various properties of these modes, of which we here just mention a few. Khare et al [42] obtained analytical solutions for a complete family of intermediate solutions, Cuevas and Eilbeck [13] studied discrete soliton interactions, Melvin et al [49] found, as mentioned above, radiationless travelling waves at "special" velocities, and Naether et al [57] analyzed the PN potential landscape in the stability exchange regimes using a constraint method to be described in the next section. We will also return to discuss the 2D version of the saturable DNLS and its mobility properties in the next section.…”
Section: Pn-barriers and Discrete Soliton Mobility In 1dmentioning
confidence: 99%